COMPOSITION AND TECHNOLOGY OF LOWER DANUBE KAOLIN WARE (LDKW): Examples from Novae, Bulgaria - With a contribution by Silviu Rădan - Daszkiewicz, Małgorzata; Bobryk, Eva; Schneider, Gerwulf (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper deals with the results of laboratory analysis carried out on 13 pottery samples from the Roman castrum of Novae, situated on the right bank of the River Danube, formerly Moesia Inferior, currently Northern Bulgaria. Three samples from the aforementioned 13 fragments were analysed (DASZKIEWICZ ET AL. 2006) as part of a project carried out for the purposes of E. Klenina’s doctoral thesis (KLENINA 2006). This pottery assemblage (totalling 72 sherds) was recovered from excavations conducted at Novae by the archaeological expedition team from Poznań’s Adam Mickiewicz University, led by A. B. Biernacki. The other ten pottery sherds discussed in this report came from excavations carried out by the Archaeological Research Centre of the University of Warsaw, under the direction of Prof. P. Dyczek.